The amygdala and medial prefrontal cortex: partners in the fear circuit. (9th April 2013) - Marek, Roger; Strobel, Cornelia; Bredy, Timothy W.; Sah, Pankaj
<x xml:space="preserve">Abstract</x> Abstract Fear conditioning and fear extinction are Pavlovian conditioning paradigms extensively used to study the mechanisms that underlie learning and memory formation. The neural circuits that mediate this learning are evolutionarily conserved, and seen in virtually all species from flies to humans. In mammals, the amygdala and medial prefrontal cortex are two structures that play a key role in the acquisition, consolidation and retrieval of fear memory, as well extinction of fear. These two regions have extensive bidirectional connections, and in recent years, the neural circuits that mediate fear learning and fear extinction are beginning to be elucidated. In this review, we provide an overview of our current understanding of the neural architecture within the amygdala and medial prefrontal cortex. We describe how sensory information is processed in these two structures and the neural circuits between them thought to mediate different aspects of fear learning. Finally, we discuss how changes in circuits within these structures may mediate fear responses following fear conditioning and extinction.